#TITLE_ALTERNATIVE# - ANITA CHRISTIANI SILALAHI SIGIRO (NIM : 12506029),
Zirconia (ZrO2) is an important material because of its use for advanced ceramic products. Pure zirconia exists in three crystal phases namely monoclinic, tetragonal, and cubic at different temperatures. The transformation from tetragonal to monoclinic is rapid and is accompanied by a 3 to 5 percent volume increase that causes extensive cracking in the material. This behavior destroys the mechanical properties of fabricated components during cooling and makes pure zirconia useless for any structural or mechanical application. Yttria-stabilized zirconia (YSZ) is a zirconium-oxide based ceramic, in which the particular crystal structure of zirconium oxide is made stable at room temperature by an addition of yttrium oxide. One of the uses of YSZ is as solid electrolyte in solid oxide fuel cell (SOFC). Therefore the application of SOFC electrolyte in the form of a thin layer then the fabrication process of thin layer is very influential in determining the properties of the electrolyte. The experiment started with the preparation of ZrO2 powder from ZOC (zirconia oxychloride) and calcination 8YSZ powder from ZrO2 and 8 mol% Y2O3. After that, 8YSZ powder was fabricated by tape casting method to obtain 8YSZ thin layer. Then the 8YSZ thin layer was sintered to a temperature 1500oC to get a stable crystal structure. A series of qualitative and quantitative tests and observations conducted to study the linear shrinkage process, densification, hardness, crystal system, and microstructure of the 8YSZ thin layer formed from the sintering process. The result of tape casting and sintering experiments showed that the zirconia crystal structure can be stabilized by the addition of yttria which is dominated by the cubic crystalline phase based on the results of XRD analysis. SEM observations showed that the thin layer has a high porosity. The results of the average densification calculation of thin layer is 35,66 % and the average thickness measurement is 0,2395 mm. Vickers hardness testing result and the calculation of the fracture toughness value are obtained respectively 137,85 HVN and 7,287 MPa.m1/2. 8YSZ thin layer has met the criteria of solid electrolyte for the thickness and crystal structure. However, densification, hardness, and fracture toughness of 8YSZ thin layer needs to be improved to meet the criteria of solid electrolyte.